Perspektif Ekonomi Islam terhadap Jual Beli Online Pakaian Bekas Impor pada Akun Instagram @hum2ndstuff - Wicaksono, Emilianasari Putri (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2021)
The study discusses the issue of buying and selling imported clothing online from the perspective of the islamic economy, which asa Muslim when engaging in activities must qualify and provide guidelines in order to make the activity legitimate or lawful according to religion. It is similar with sales in which to qualify and be reconciled to those who are selling and buying. The purpose of the study is to find out how the practice of selling imported goods online is done by the @hum2ndstuff according to the islamic economic perspective. This type of research method involves qualitative methods using data collection methods that are done, interviews and reference searches with library materials (books, magazines, newspapers, media, and the Internet, research published and others) to facilitate the research process. The results of this study are known to have been the practice of buying and selling used clothing online between traders and agents with direct purchases to distributors, then retailers via social media. The system of exchange carried out by the instagram account @hum2ndstuff is allowed because it qualifies and is good at selling and selling, with clothes being sold by prospective buyers, it also contains no negative elements.